Evaluating OutLoud!: A CEFR-Based Digital Game for EFL Speaking Instruction - Sulistya Ningrum; Risnawati; Ahmad Iman Mulyadi; Rani Aziza; Suci Wasilah Urwatul Zahra; Fauzan Dwi Purdani (Raja Zulkarnain Education Foundation, 2026)
This study aimed to evaluate the effectiveness of a CEFR-based situational dialogue game, OutLoud!, in improving EFL learners’ speaking competence. The research was conducted at Goolin Indonesia, a non-formal English education institution in Palembang, over several instructional sessions. The population consisted of EFL learners enrolled in the institution, with a sample of 20 participants ranging from A2 to C1 proficiency levels. The study employed a quasi-experimental one-group pre-test–post-test design. Data were collected using three instruments: a speaking test, a questionnaire, and classroom observation. The speaking test, administered before and after the intervention, assessed learners’ performance based on CEFR-aligned criteria, including fluency, grammatical accuracy, vocabulary, pronunciation, and interaction. The questionnaire used a 5-point Likert scale to measure learners’ engagement, motivation, and confidence, while observations were conducted to document participation and interaction during the learning process. Data analysis was conducted using descriptive statistics, including mean scores and percentage improvement, supported by qualitative observations. The results showed that learners’ speaking performance improved from a mean score of 62.40 in the pre-test to 75.50 in the post-test, indicating a 21% increase. In addition, questionnaire results revealed high levels of engagement (M = 4.32), motivation (M = 4.45), and confidence (M = 4.28). These findings suggest that the integration of CEFR, gamification, and situational dialogue in a digital game environment can effectively enhance speaking competence and create a positive learning experience in non-formal EFL contexts.